ANALISIS NILAI KONSELING ISLAM DALAM KITAB RISALATUL MU’AWANAH KARYA HABIB ABDULLAH BIN ALWY AL-HADDAD - Zainul Rhofik; Mohamat Hadori (Fakultas Dakwah Universitas Ibrahimy, 2023)
There have been many counseling practices that are generally said to be good, but the standardization of the good opinion still does not reflect the good nature itself, such as practices that do not reflect commendable morals but are considered mediocre, counselors who are easily emotional in serving clients. One of the causes of this unhealthy counseling is the lack of morals and tasawwuf from the counselor in managing and serving the counselee properly which results in the counseling process not as desired. This study aims to describe the analysis of the value of Islamic counseling in the Risalatul Mu’awanah book by Habib Abdullah bin Alwy Al-Haddad. The research method used is a qualitative research method with the type of hermeneutic research, hermeneutics is an activity of interpreting an object that has meaning, with the aim of bringing out objective possibilities in the literature studied. From the research results, there are 12 Islamic counseling values contained in the Risalatul Mu’awanah, namely: (1) confidence, (2) having good intentions, (3) muraqabah, (4) time management, (5) wara’, (6 ) fair, (7) devoted to parents, (8) repentance, (9) patient in accepting destiny, (10) patient in carrying out God’s commands (11) resignation and, (12) holding fast to the book and As-sunnah. Keywords: the value of Islamic counseling, the book of risalatul mu’awanah